Asymmetric Electrosorption in a Bio-Inspired Reactor Enables Energy Efficient Ocean Carbon Removal - Yifang Zhu; Jundong Wang; Ou, Yang; Fuhrman, Jay; Ji, Haodong; Meng Lin; Yandi Hu; Juan Liu; Zuo, Kuichang; Huazhang* Zhao; Zishuai* Zhang (Angewandte Chemie International Edition, 2025)
Ocean carbon removal represents a promising pathway for mitigating residual anthropogenic carbon dioxide (CO2), yet existing methods are constrained by high energy demands and potential ecological risks. Here, inspired by the natural calcification process of corals, we present a bio-inspired capacitive decarbonization (CDC) reactor that sequesters dissolved inorganic carbon (DIC) from seawater as CaCO3 using only seawater-derived Ca2+ and renewable electricity. The CDC system integrates a Ca2+-selective electrode with a weak electric field to regulate ion transport and disrupt the hydration shell of Ca2+, enhancing its reaction with CO32−. To address the limited concentration of CO32− relative to Ca2+ in seawater, we introduce an asymmetric electrosorption strategy to preferentially enrich CO32− at the electrode interface, achieving a DIC conversion rate of up to 34% with an ultralow intrinsic electrochemical energy input of 2.5 kJ mol−1 CO2 for the CDC reactor. The reactor exhibits stable continuous operation for over 100 h without fouling, enabled by spatially decoupled CaCO3 precipitation. To mitigate the reduction in seawater alkalinity, we introduce a mineral-assisted re-alkalinization step that effectively restores pH and supports continued CO2 absorption. A global integrated analysis model shows the CDC technology could remove up to 11–438 million tonnes of CO2 by 2050–2100. This work demonstrates a scalable and low-energy solution for durable ocean carbon removal.